2021
DOI: 10.1177/14407833211031292
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing work–family enrichment as a separated parent in Australia

Abstract: Contrary to approaching work and family as conflictual roles, a shift towards acknowledgement of the positive interaction between work and family has been detected. This research investigated whether married/cohabiting and divorced/separated parents differ in terms of work–family enrichment, considering their gender and relationship status after separation. Data from 3993 married/cohabiting and 1455 divorced/separated parents from the Longitudinal Study of Australian Children (LSAC) database were analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Work-family conflict causes stress, burnout, low life and marital satisfaction, and various health problems (such as sexual dysfunctions) for the individual. Work-family conflict stems from reasons such as irregular working hours, working conditions, quality time spent with family, spousal support, communication, and sexual life [12,71].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Work-family conflict causes stress, burnout, low life and marital satisfaction, and various health problems (such as sexual dysfunctions) for the individual. Work-family conflict stems from reasons such as irregular working hours, working conditions, quality time spent with family, spousal support, communication, and sexual life [12,71].…”
Section: Discussionmentioning
confidence: 99%
“…These are the work environment, desiring to be loved/sexuality, and the social environment. There is a relationship between leisure time and life satisfaction, and between job satisfaction and life satisfaction [12]. Sexual life satisfaction impacts couples' married lives [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that women have higher levels of work-family enrichment than men. Authors such as Van Den Eynde and Mortelmans (2021) have corroborated this and also emphasized that single mothers experience greater levels of work-family enrichment after a separation, when compared with married women. However, there are studies that did not find gender differences in the behavior of individuals (Kim, Shigemoto, Neduvelil & Grzywacz, 2021), leaving room for further investigation.…”
Section: Introductionmentioning
confidence: 77%